An update on the development of mine closure and reclamation standards by the International Organization for Standardization - Murphy, DP; Nahir, M; Didier, C (Mine Closure 2019: 13th International Conference on Mine Closure, 2019)
The work program through the International Organization for Standardization (ISO), which aims to develop a series of international standards that will provide requirements and recommendations for mine closure and reclamation management, is now advanced, with two standards at committee draft level. In accordance with ISO timelines, these international standards are targeted for publication in 2020. Twelve countries are actively participating in development of these standards, with a further 11 countries observing. The two standards currently under development include one related to mine closure and reclamation terminology and one related to mine closure and reclamation planning of future or ongoing mines. A strategic plan has also been developed that outlines key themes under which further standards may be developed in the coming years. A new initiative within the work program concerning management and securing of orphan mines is currently under development.
Keywords: International Organization for Standardization; terminology; mine closure planning; standards